Biodegradable Hollow‐Structured Nanozymes Modulate Phenotypic Polarization of Macrophages and Relieve Hypoxia for Treatment of Osteoarthritis. Issue 32 (17th July 2022) - Xiong, Hao; Zhao, Yongzheng; Xu, Qinyuan; Xie, Xue; Wu, Jianrong; Hu, Bing; Chen, Shuai; Cai, Xiaojun; Zheng, Yuanyi; Fan, Cunyi
Abstract: Nanozymes are widely applied for treating various major diseases, including neurological diseases and tumors. However, the biodegradability of nanozymes remains a great challenge, which hinders their further clinical translation. Based on the microenvironment of osteoarthritis (OA), a representative pH‐responsive biodegradable hollow‐structured manganese Prussian blue nanozyme (HMPBzyme) is designed and applied for treatment of OA. HMPBzyme with good pH‐responsive biodegradability, biocompatibility, and multi‐enzyme activities is constructed by bovine serum albumin bubbles as a template‐mediated biomineralization strategy. HMPBzyme suppresses hypoxia‐inducible factor‐1α (HIF‐1α) expression and decreases reactive oxygen species (ROS) level in the in vitro experiment. Furthermore, HMPBzyme markedly suppresses the expression of ROS and alleviates the degeneration of cartilage in OA rat models. The results indicate that the biodegradable HMPBzyme inhibits oxidative damage and relieves hypoxia synergistically to suppress inflammation and promote the anabolism of cartilage extracellular matrix by protecting mitochondrial function and down‐regulating the expression of HIF‐1α, which modulates the phenotypic conversion of macrophages from pro‐inflammatory M1 subtype to anti‐inflammatory M2 subtype for OA treatment. This research lays a solid foundation for the design, construction, and biomedical application of biodegradable nanozymes and promotes the application of nanozymes in biomedicine. Abstract : A representative pH‐responsive biodegradable hollow‐structure manganese Prussian blue nanozyme (HMPBzyme) is designed for osteoarthritis (OA) treatment. Biodegradable HMPBzyme inhibits oxidative damage and relieves hypoxia synergistically to alleviate inflammation and cartilage degeneration by protecting mitochondrial function and downregulating the expression of HIF‐1α to modulate the phenotypic polarization of macrophages from the pro‐inflammatory M1 to the anti‐inflammatory M2 for OA treatment.